2021
DOI: 10.1002/saj2.20329
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregate‐associated organic carbon and nitrogen response to long‐term no‐till crop rotation, cover crop, and manure application

Abstract: Soil C and N sequestration using conservation practices to alleviate climate change are necessary; however, diverse crop management influences on aggregate-associated C and N levels need consideration. Our objective was to compare bulk soil and aggregate-associated C and N under cover crops hairy vetch (Vicia villosa Roth) and winter wheat (Triticum aestivum L.), poultry litter application, fallow control, and crop rotations of continuous cotton (Gossypium hirsutum L.), cotton-corn (Zea mays L.), continuous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…The application of organic fertilizer plays a substantial role in sustaining soil organic matter levels and simultaneously, the input of organic materials is also beneficial for the improvement of soil aggregate structure and available nutrients [ 68 ]. These changes further affect the distribution, abundance, activity and composition of the microbial community [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of organic fertilizer plays a substantial role in sustaining soil organic matter levels and simultaneously, the input of organic materials is also beneficial for the improvement of soil aggregate structure and available nutrients [ 68 ]. These changes further affect the distribution, abundance, activity and composition of the microbial community [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pH range of soils in the Sushui River Basin is 7.5−9; when the pH value is in the 6−8 range, it is favorable for biodiversity. This can promote crop growth to improve straw return and maintain soil aggregate stability, thereby promoting SOC sequestration [12][13][14][15][16]. When the average rainfall is 600-1000 mm, crop rotation can significantly promote SOC growth [12].…”
Section: Spatial Heterogeneity Of the Effect Of Wheat And Maize Crop ...mentioning
confidence: 99%
“…As one of the principles of conservation agriculture, crop rotation has received widespread attention because of its ecological functions, such as mitigating soil degradation and slowing down Land 2024, 13, 859 2 of 14 SOC loss [12]. In a meta-analysis conducted by Zheng et al [12], crop rotation was shown to be able to enhance SOC in general as it can keep the ground covered, increase soil biodiversity, and boost the number of agglomerates and, in turn, organic C content [13][14][15][16]. Cover cropping can increase soil vigor by increasing the SOC content and crop yield [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that although macroaggregates have a greater capacity to contain SOC and TN, these soils, highly degraded due to a long history of unsustainable management, have lost the majority of the SOC-S available in macroaggregates, which are extremely sensitive to management alterations and are easily disrupted. In contrast, microaggregates were the largest reservoir of SOC in these soils because they provide physical protection to the SOC, thus promoting the long-term fixation of SOC into the soil [85][86][87]. In this regard, the sustainable management practices aimed at increasing C stocks and C sequestration in agricultural soils should encourage the development and preservation of macroaggregates in line with Zheng et al [88], whose evaluation and monitoring can serve as a key parameter in the impact assessment of the implemented crop management and diversifications.…”
Section: Soc Stock and Aggregate-associated C And Nmentioning
confidence: 99%